2021
DOI: 10.1021/acsami.1c06087
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Lignin Particles and Epoxies for Bio-Based, Durable, and Multiresistant Nanostructured Coatings

Abstract: There is a need for safe and sustainable alternatives in the coating industry. Bio-based coatings are interesting in this perspective. Although various oils and waxes have been used as traditional wood coatings, they often lack sufficient durability. Lignin is an abundant natural polyphenol that can be used to cure epoxies, but its poor water solubility has impeded the use of unmodified lignin in coatings in the past. To address this issue, water-dispersible colloidal lignin particles (CLPs) and an epoxy compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. From Table 5, the predictions of the finite element method were found to be close to the experimental results in some simulations but diverged in others.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. From Table 5, the predictions of the finite element method were found to be close to the experimental results in some simulations but diverged in others.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 65%
“…It is reported that decreased coating weight generates higher hydrophobicity and surface roughness while thick layers come with fewer empty spaces between the layers, resulting in a reduced hydrophobic effect. In addition, thin layers of filament are most likely to retain the intrinsic unevenness of the surface [34,35]. Some studies reported on the extensive hydrophobic nature of thin coating related to the higher roughness [36], while other studies [37] suggested decreased surface roughness as well as hydrophobicity due to filled up voids and formation of large aggregate in the case of multiple layers.…”
Section: Simulations and Experimental Resultsmentioning
confidence: 99%
“…Compared to kraft lignin, both EKL and EKL:LNP showed significantly increased thermal stability (Table 2) especially at temperatures above 400 °C, which is unseen in studies where an epoxy with longer chain length is used. 27,57 One reason may be the high density of thermally stable aromatic structures that the short cross-link bridges enable. The low mass loss of EKL: LNP composites upon heating suggested that the material may possess flame resistance, which was hence tested with a Bunsen burner at close range to wooden surface coated with EKL:LNP.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…[ 29 ] Beyond the foam synthesis, some other studies showed a total conversion of PHU with fast kinetics and catalyst‐free. [ 45–47 ] Additionally, thio‐cyclic carbonate or dithiocarbonate (DTC) have been first synthesized using carbon disulfide instead of CO 2 , in one step synthesis, by Endo et al. [ 48 ] who demonstrated their high reactivity.…”
Section: Introductionmentioning
confidence: 99%